KAJIAN TELAAH PLACE IDENTITY DALAM KONTEKS INTERIORITAS: KAJIAN TELAAH PLACE IDENTITY DALAM KONTEKS INTERIORITAS - doddy friestya asharsinyo; Ully Irma Maulina Hanafiah (Ide dan Dialog Desain Indonesia (Idealog), 2025)
Abstract: The term "place identity" is open to multiple interpretations because it applies both to the identity of a place and to the identity of people and their process of identifying with that place, two elements that are both socially constructed and develop reciprocally, both among themselves and with the place itself. In the context of interior spaces, which have an enclosure and a defined spatial content with clear boundaries and positions, the concept of place identity is often associated with the brand identity of a commercial enterprise or service provider. This study aims to examine the concept of place identity by identifying various relevant discussions and classifying them based on the levels of place identity dimensions ranging from individual to communal interpretations of interior spaces, to broader scales related to brand/corporate identity and place image. The research was conducted using a systematic concept analysis approach to formulate a broad and comprehensive definition, by reviewing the literature to identify similarities and differences among concepts, and to develop a formulation of place identity that can represent identity within the context of interiority The research findings identified three main components that shape place identity in the context of interior spaces: the physical environment, activity, and meaning. These three components provide a conceptual framework for explaining the process of place identity formation in interior spaces. Keywords : Place identity, Activity, Physical environment, Meaning, Interiority